Intraperitoneal ropivacaine for post-operative pain following laparoscopic tubal ligation: a randomised double-blind placebo-controlled trial - Jerilee Mariam Khong Azhary; Aizura Syafinaz Adlan; Sivakumar S. Balakrishnan; Siti Rohayu Kamarul Baharain; Syeda Nureena Syed Jafer Hussain Zaidi; Nuguelis Razali; Mukhri Hamdan; Noor Azmi Mat Adenan; Siti Zawiah Omar (IMR Press, 2021)
Background: Female sterilisation is the most common method of contraception worldwide and laparoscopic tubal sterilisation is increasingly considered as a day-surgery procedure. Therefore, pain following this procedure should be seriously addressed. Instillation of 200 to 300 mg of ropivacaine intraperitoneally has been proven effective in controlling pain after laparoscopic tubal ligation (LTL). However, extreme caution must be taken as potential serum toxicity has been reported with the instillation of 150 mg of intraperitoneal ropivacaine. In search of the lowest, most effective dose, this study aimed to evaluate the effectiveness of 112.5 mg of ropivacaine intraperitoneally in reducing post-operative pain after LTL. Methods: This double-blind, placebo-controlled randomised trial was conducted in an ambulatory care centre in Malaysia. Sixty-two patients scheduled for LTL were recruited. Two patients were excluded from the trial because of intraoperative complications. Sixty patients were randomised to either the placebo group (intraperitoneal normal saline, n = 30) or the ropivacaine group (intraperitoneal ropivacaine, n = 30). Pain scores (using a visual analogue score), and the need for additional analgesia were assessed at 15, 60, 120, and 240 minutes post-LTL. Results: We observed no significant differences in pain scores or the need for additional analgesia between the groups. Conclusion: 112.5 mg of ropivacaine administered intraperitoneally is not more effective than normal saline in decreasing post-operative pain after LTL.